Sn-PILC: A novel Efficient and Recyclable Catalyst for One-pot Three Component Povarov’s Inverse-electron-demand Hetero Diels-Alder Reaction for a Facile Synthesis of Tetrahydropyranoquinoline Derivatives under Neat Conditions - Rai, Megha; Jadhav, Shivaji; Farooqui, Mazahar (Orbital: The Electronic Journal of Chemistry, 2016)
The Povarov’s inverse-electron-demand hetero Diels–Alder one-pot three components reaction of aromatic aldehyde, aromatic amine with DHF has been developed using Sn-PILC as a catalyst under a neat condition which may helpful to society to get pharmacologically more active compounds. In the present study a novel series of tetrahydroquinoline 4(a-f) were synthesized and characterized by IR, 1HNMR, 13CNMR, Mass spectral analysis and elemental analysis. The synthetic details and characterization results are discussed. DOI: http://dx.doi.org/10.17807/orbital.v8i3.801